Towards a Bergsonian reading of Le Bal des voleurs by Jean Anouilh - Voždová, Marie; Matoušková, Jiřina (Romanica Olomucensia, 2019)
The play The Thieves' Carnival (Le Bal des voleurs) by the French playwright Jean Anouilh, written in 1938 and published in the set of "Pink Plays" in 1942, occupies an exceptional place in the theatrical universe of the author, as it is his only comedic ballet. In this paper, the different aspects of Anouilh's laughter and sense of the comic reflected by the behaviour of the characters featured in the play are shown. In order to perform a detailed thematic analysis, several theoretical approaches to the category of comedy are followed, including the famous thesis by Henri Bergson entitled Laughter. An Essay on the Meaning of the Comic, published in 1900. The application of Bergson's theory to The Thieves' Carnival shows that Anouilh's sense of the comic is based on three types of comic situations which were defined by Bergson. On the basis of these situations, it is possible to identify the principles of repetition, inversion, and mutual interconnection of situations. Given that the sense of the comic present in the works of Anouilh as a whole is fused with elements of the tragic and is identified as an existential bitter type of comedy, the comedy The Thieves' Carnival can be considered an exception. Nevertheless, Anouilh's comedy bears traces of melancholy and sadness created by the heaviness of existence, even in this pleasant distraction.
Keywords: laughter; situation comedy; character; Anouilh; Bergson